Sustainable Affordable Housing: State-Of-The-Art and Future Perspectives - Vasco-Calle, D (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Nowadays, there are many studies with a significant focus on affordable housing. The relevance of this theme, which is usually the central object of public housing policies, requires an updated review of the problems and challenges to be overcome, especially in terms of sustainability, in favor of an improvement in the quality of products delivered to beneficiaries. This research concentrates on applying the sustainability concept to affordable housing, emphasizing technical, social, and governance aspects. A novel classification framework is introduced, encompassing these aspects in the context of sustainability integrated with affordable housing. A systematic literature review is conducted and more than 100 articles are examined based on bibliometric and bibliographic analyses to highlight the main dimensions and topics involved in the housing public policy sphere. The study has been elaborated based on collecting relevant materials, building a descriptive analysis of the literature examined, highlighting the classification structure that categorizes the studies examined, and evaluating the material identified based on the classification structure. The outcomes aim to spotlight the diverse dimensions of sustainable affordable housing and associated research themes. Furthermore, the research outlines deficiencies in current approaches and outlines a future research agenda for implementing sustainability in affordable housing. It establishes a strong connection between technical, social, and governance aspects of affordable housing and sustainability, considering anticipated approaches, techniques, and challenges. © 2024 by the authors.